(untitled) (Journal of Advanced Research in Social Sciences, 2024)
This research article will present findings from an intertextual study of EU member states’ Diversity Charter (DC) initiatives. With the aid of thematic analysis, we undertook this intertextual analysis of DCs to study and compare their content. We also consider the political and social context in which the DCs operate. In this regard, the research also evaluates how principles set by the EU Charter of Fundamental Rights are enacted in law by member states and why there is a need for expanding human rights guarantees with initiatives like the DC. Our findings conclude with five points about the current state of DC initiatives in EU member states. Furthermore, based on the findings and our professional experience, we note the critical areas of improvement that can be made to the existing DC. The article concludes with our proposal for developing the Reflective Realignment Approach to help companies create a more inclusive work environment.